Semi-Totally Semi-Continuous Functions in Topological Spaces - Hula .M Salih (Al-Qadisiyah Journal of Pure Science, 2017)
In this paper ,we introduce and study a new generalization of continuity called semi-totally semi-continuity ,which is stronger than semi-continuity and weaker than semi-totally continuity is introduced and studied "Further ,some properties of these functions are investigated .Also semi-totally semi-open functions in topological spaces are introduced and studied.